Impact of socioeconomic status on cardiac arrest outcomes during COVID-19 pandemic - Soonjoo Wang; Hang A. Park; Sangsoo Han; Ju Ok Park; Sola Kim; Choung Ah Lee (Heliyon)
Introduction: The coronavirus disease 19 (COVID-19) pandemic has affected healthcare services, potentially leading to inequitable outcomes based on patients’ socioeconomic status (SES). This study aimed to evaluate the impact of COVID-19 on out-of-hospital cardiac arrest (OHCA) outcomes by examining disparities across SES levels. Methods: The study analyzed non-traumatic OHCA cases registered in the Korean Out-of-Hospital Cardiac Arrest Registry from 2010 to 2021, encompassing 238,668 patients aged 18 years and older. SES was assessed at both the individual (Medicaid vs non-Medicaid) and area levels using a deprivation index. Outcomes included any return of spontaneous circulation, survival to admission, survival to discharge, and favorable neurological recovery. Logistic regression and generalized additive models (GAMs) were used for analysis. Results: OHCA outcomes—including survival to admission, survival to discharge, and favorable neurological recovery—improved over the years, peaking in 2019 before subsequently declining. Logistic regression showed that the lowest SES area was associated with lower rates of ROSC (adjusted odds rations [aOR] 0.82, 95 % confidence interval [CI] 0.75–0.88) and survival to admission (aOR 0.56, 95%CI 0.49–0.64) and discharge (aOR 0.78, 95%CI 0.61–0.98) during the pandemic. GAM analysis revealed that lower SES groups (deprivation index levels 4 and 5) experienced higher-than-expected survival to admission and discharge rates, as well as favorable neurological recovery. Although outcomes in the deprivation index level 1 group (5.5 % in 2021) remained superior, indicating poor outcomes for the lowest SES area group (3.43 % in 2021), the disparity decreased following the pandemic. Conclusion: Lower levels of SES are a significant risk factor for unfavorable neurological recovery in OHCA, independent of the COVID-19 pandemic. However, SES-related disparities in the outcomes decreased post-pandemic. Despite the overall negative impact of COVID-19, certain lower SES groups showed improved survival rates, likely due to differences in the EMS response and healthcare burden across regions.